Effect of Exhaust Gas Recirculation in NOx Control for Compression Ignition and Homogeneous Charge Compression Ignition Engines. (2015) - Pratheeba, C.N.; Aghalayam, Preeti
Abstract: Exhaust Gas Recirculation (EGR) is a potential option for controlling in-cylinder NOx in automobiles. This paper aims to study the effect of EGR on NOx emissions and in Compression Ignition (CI) engines at various conditions. To this end, low dimensional models are developed using a first principles approach without recourse to empirics. Fuel oxidation represented by a three-step global kinetic model coupled with the Zeldovich mechanism for NOx formation is used to predict the composition of the entire spectrum of engine-out gases. Solution of the conservation equations using MATLAB provides the in-cylinder variation of parameters like volume, pressure, torque, speed and work done and species (Fuel, CO, CO2, NOX, etc.) with respect to Crank Angle Displacement (CAD). The inlet conditions are the fuel-air equivalence ratio, engine specifications and the inlet air temperature. The simulations are validated against experimental pressure profiles from the literature. External EGR is then implemented to study its effect on engine-out emissions under cold start conditions. The effect of EGR at various combinations of engine operating conditions is examined in detail.